Some issues of legal regulation of energy security in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
In this article, one of the most topical issues of ecological law concerning energy security is comprehensively and complex considered. The content of international and national legislation is examined. One of the main directions of the state strategy of energy security is the acceleration of the development of renewable energy sources and advanced technologies. In the course of the study, recommendations for improving the current legislation as well as theoretical conclusions were prepared.The methodological basis of the article was a comparative legal method, formal-logical, system-structured analysis, scientific abstraction, unity of objective and subjective in the development of legal processes, expert evaluation, analysis of documents and materials.The article reveals the main directions of the state energy policy and suggests measures to create a system of regulatory support for its implementation. The author pays much attention to the introduction and legal regulation of renewable and alternative energy sources.Key words: environmental safety, energy security, legal regulation, energy policy of the state.